2020
DOI: 10.1159/000506665
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNAs Profile in Children’s Nonalcoholic Fatty Liver Disease and the Correlation with Transaminase and Uric Acid

Abstract: Objective: The incidence of non-alcoholic fatty liver disease (NAFLD) in children increased rapidly. However, the pathogenesis of NAFLD, especially how non-alcoholic fatty liver progress to non-alcoholic steatohepatitis, is still unclear. This study aims to explore the exosomal miRNAs profiles and the underline pathogenesis of child NAFLD. Methods: Twenty NAFLD and 20 health control were enrolled in this study. Circulating exosomes were isolated, and RNA sequencing was performed in test set (3 NAFLD/3 Controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, the sensitivity of ultrasound for the detection of mild steatosis is 60.9%-65% ( 18 , 19 ). Thus, alternative noninvasive strategies, such as serum biomarkers (ALT/AST ratio, APR Index, BARD score, NAFLD fibrosis score, FIB-4 index, exosomal miRNAs), and imaging techniques (elastography) have made great strides over the past decade ( 20 , 21 ). Other cardiometabolic risk factors, such as triglyceride glucose-waist circumference(TyG-WC), triglyceride glucose-body mass index(TyG-BMI), triglyceride glucose-waist-to-height ratio(TyG-WHtR), waist-to-hip ratio(WHR), waist-to-height ratio(WHtR), and homeostatic model assessment of insulin resistance(HOMA-IR) have also been reported to be suitable predictors of NAFLD ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the sensitivity of ultrasound for the detection of mild steatosis is 60.9%-65% ( 18 , 19 ). Thus, alternative noninvasive strategies, such as serum biomarkers (ALT/AST ratio, APR Index, BARD score, NAFLD fibrosis score, FIB-4 index, exosomal miRNAs), and imaging techniques (elastography) have made great strides over the past decade ( 20 , 21 ). Other cardiometabolic risk factors, such as triglyceride glucose-waist circumference(TyG-WC), triglyceride glucose-body mass index(TyG-BMI), triglyceride glucose-waist-to-height ratio(TyG-WHtR), waist-to-hip ratio(WHR), waist-to-height ratio(WHtR), and homeostatic model assessment of insulin resistance(HOMA-IR) have also been reported to be suitable predictors of NAFLD ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 30 ) demonstrated decreased liver and serum miR-155 levels in adult patients with NAFLD, Zhou et al. ( 31 ) showed increased serum levels in children with NAFLD. In the current study, we found positive correlations between serum miR-155 level and insulin and adiponectin concentrations in children with IR regardless of NAFLD status, and IHTG and liver enzymes in children with NAFLD only.…”
Section: Discussionmentioning
confidence: 98%
“…MicroRNA-122 is associated with IR, inflammation and adiposity in overweight adults and regulates insulin signaling pathways, as revealed by functional analysis [58]. Moreover, the exosomal microRNA profile correlates with BMI, transaminases and uric acid in children with non-alcoholic fatty liver disease (NAFLD) [59] and differs between healthy and BMI-matched T2DM humans, who display higher levels of microRNA-20b-5p, which modulates the Akt signaling when transfected in SkM cells [60]. People with T2DM display also upregulation of microRNA-144 and downregulation of its predicted target IRS1, which supports the relevance of microRNA-144 for T2DM development [61].…”
Section: Micrornamentioning
confidence: 99%